Looking for loons - Lloyd, Jennifer (Simply Read Books, 2007)
Just after sunrise, a boy ventures out onto the front porch of the family cottage to scan the misty lake through an old pair of binoculars. He is looking for loons. Joined by other pajama-wearing family members and sipping a steaming mug of hot chocolate, he experiences nature's magical sights and sounds firsthand. Jennifer Lloyd's sensitive prose and Kirsti Wakelin's shimmering artwork bring to life such enchanting images as a beaver smacking his tail in water and a canoe gliding serenely in the distance in this memorable picture book.